Surveying Surveys and Questioning Questions : Learning from World Bank Experience - Xu, Lixin Colin 1997- (The World Bank, 1999)
March 2000 - How to make firm-level surveys more consistent, yielding data more relevant to policy analysis. The World Bank has increasingly focused on firm-level surveys to build the data foundation needed for accurate policy analysis in developing and transition economies. Recanatini, Wallsten, and Xu take stock of some recent Bank surveys and discuss how to improve their results. Lessons on data issues and hypothesis testing: · Use panel data, if possible. · Have enough information about productivity to estimate a production function. · Avoid the paradigm of list the severity of the obstacle/problem on a scale of 1 to 5. Instead, ask for data on specific dimensions of the problem that will shed light on alternative hypotheses and policy recommendations. · Pick particular disaggregated industries and sample those industries in each survey. · Identify the most important policy interventions of interest and consider how you will empirically identify specific changes by picking instruments useful for doing so. Lessons on questionnaire design: · Incorporate only one idea or dimension in each question. Do not ask, in one question, about the quality, integrity, and efficiency of services, for example. · Consider the costs and benefits of numeric scales compared with adjectival scales. Scales in which each point is labeled may be more precise than numeric scales in which only the endpoints are labeled. But responses are very sensitive to the exact adjective chosen and it may be impossible to translate adjectives precisely across languages, making it impossible to compare responses across countries. · Recognize that the share of respondents expressing opinions will be biased upward if the survey does not include a middle (indifferent or don't know) category and downward if it does include the middle category.